The role of technology in enhancing financial reporting (a case study of banks in embu county) - MULI, ANNASTACIA MUTINDI (UoEm, 2024)
This research project aimed to examine the role of technology in enhancing financial reporting in banks in Embu County, Kenya. The increasing adoption of digital technologies in the financial industry has led to improvements in financial reporting processes. The study focused on the extent of technology adoption in financial reporting in banks in Embu County, the benefits and challenges experienced, and the impact on the quality of financial reporting. Qualitative research methods were used to gather data from key stakeholders in the banking industry, including bank management, regulators, and investors. The findings of this research provided insights into the importance of technology in enhancing financial reporting and informed future investment decisions in technology for banks in Embu County. The results were also valuable for other financial institutions and regulators in the region and beyond